BROMETH: Methodology to design safe reconfigurable medical robotic systems. Issue 3 (14th November 2016) - Ben Salem, Mohamed Oussama; Mosbahi, Olfa; Khalgui, Mohamed; Jlalia, Zied; Frey, Georg; Smida, Mahmoud
Abstract: Background: This research paper deals with the development of a medical robotized control system for supracondylar humeral fracture treatment. Concurrent access to shared resources and applying reconfiguration scenarios can jeopardize the safety of the system. Methods: A new methodology is proposed in this paper, termed BROMETH, to guarantee the safety of such critical systems from their specification to their deployment, and passing through certification and implementation. The solution is applied to a real case study named Browser‐based Reconfigurable Orthopedic Surgery (abbrev. BROS), a robotized platform dedicated to the treatment of supracondylar fractures, to illustrate the paper's contribution. This work starts from a medical issue, namely supracondylar humeral fracture treatment, to establish a new informatics solution, namely a new methodology to design safe reconfigurable medical robotic systems. Results: The results of the experiments performed on real SCH fracture radiographies were quite satisfactory. Conclusions: Clinical experiments can then be performed after deploying the system on real hardware.